Gender Disparities in Alcohol Use Disorder Treatment Among Privately Insured Patients with Alcohol‐Associated Cirrhosis. (22nd January 2019) - Mellinger, Jessica L.; Fernandez, Anne; Shedden, Kerby; Winder, G. Scott; Fontana, Robert J.; Volk, Michael L.; Blow, Frederic C.; Lok, Anna S. F.
Abstract : Background: The burden of alcohol‐associated cirrhosis (AC) is high, and though alcohol cessation improves mortality, many patients fail to engage in alcohol use disorder (AUD) treatment and continue drinking. Our aim was to determine rates, predictors, and outcomes of AUD treatment utilization in AC patients with private insurance. Methods: We collected data from persons with AC (diagnosed by ICD‐9/ICD‐10 codes), aged 18 to 64 years, enrolled in the Truven MarketScan Commercial Claims and Encounters database (2009 to 2016). We determined rates and predictors of substance abuse treatment visits as well as rates of alcohol relapse prevention medication prescriptions, weighted to the national employer‐sponsored insured population. Effects of AUD treatment utilization on decompensation rates were calculated using proportional hazards regression with propensity score adjustment. Results: A total of 66, 053 AC patients were identified, 32% were female, and mean age at diagnosis was 54.5 years. About 72% had insurance coverage for substance abuse treatment. Overall, AUD treatment utilization rates were low, with only 10% receiving a face‐to‐face mental health or substance abuse visit and only 0.8% receiving a Food and Drug Administration (FDA)‐approved relapse prevention medication within 1 year of index diagnosis. Women were less likely to receive a face‐to‐face visit (hazard ratio [HR] 0.84, p  < 0.001) or an FDA‐approved relapse prevention medication (0.89, p  = 0.05) than men. AC patients who had a clinic visit for AUD treatment or used FDA‐approved relapse medication showed decreased risk of decompensation at 1 year (HR 0.85, p  < 0.001 for either). Conclusions: AUD treatment utilization is associated with lower decompensation rates among privately insured patients with AC. Women were less likely to utilize AUD treatment visits. Efforts to reduce gender‐specific barriers to treatment are urgently needed to improve outcomes. Abstract : Access to alcohol use treatment is critical for those with alcohol‐associated liver disease as alcohol cessation improves outcomes. In this study of a large population of privately insured US adults with alcohol‐associated cirrhosis, access to alcohol use treatment was low, and access to all forms of alcohol use treatment was lower in women compared to men. Those who received treatment were less likely to experience symptoms of cirrhosis. Future studies should determine how to improve rates of alcohol use treatment for those with alcohol‐associated cirrhosis.